Anti-Proliferative Effects of Siegesbeckia orientalis Ethanol Extract on Human Endometrial RL-95 Cancer Cells - Chi-Chang Chang; Hsia-Fen Hsu; Kuo-Hung Huang; Jing-Mei Wu; Shyh-Ming Kuo; Xue-Hua Ling; Jer-Yiing Houng (Molecules, 2014)
Endometrial cancer is a common malignancy of the female genital tract. This study demonstrates that Siegesbeckia orientalis ethanol extract (SOE) significantly inhibited the proliferation of RL95-2 human endometrial cancer cells. Treating RL95-2 cells with SOE caused cell arrest in the G2/M phase and induced apoptosis of RL95-2 cells by up-regulating Bad, Bak and Bax protein expression and down-regulation of Bcl-2 and Bcl-xL protein expression. Treatment with SOE increased protein expression of caspase-3, -8 and -9 dose-dependently, indicating that apoptosis was through the intrinsic and extrinsic apoptotic pathways. Moreover, SOE was also effective against A549 (lung cancer), Hep G2 (hepatoma), FaDu (pharynx squamous cancer), MDA-MB-231 (breast cancer), and especially on LNCaP (prostate cancer) cell lines. In total, 10 constituents of SOE were identified by Gas chromatography-mass analysis. Caryophyllene oxide and caryophyllene are largely responsible for most cytotoxic activity of SOE against RL95-2 cells. Overall, this study suggests that SOE is a promising anticancer agent for treating endometrial cancer.